Yield trends and apparent nutrient balances in intensified and diversified rice-based cropping systems - Pascua Jr, S.R.; Ventura, W.; Agustin, E.O.; Padre, A.T.; Valencia, D.A.; Marcos, T.F.; Sta. Cruz, Pompe C.; Obien, S.R.; Ladha, J.K. (Cambridge University Press, 1999)
A long-term field trial was conducted to determine yield trends in relation to nutrient uptake and efficiency in different rice-based cropping systems. The cropping systems had a significant effect on wet season rice yield when residues were not recycled but had no effect otherwise. Rice yield decreased after the first year of crop residue incorporation but increased every year thereafter. Rice yield was significantly affected by residual nutrients applied to dry season crops. The highest residual effect was observed in tomato and sweet pepper to which the highest nitrogen (N), phosphorus (P) and potassium (K) rates were applied. Maize, sweet pepper, and tomato responded well to NPK application, garlic had a low response and mungbean had no response. A relay crop served as a catch crop for excess nutrients and as shade to minimize sunscald effects for tomato and sweet pepper fruits.